Implementasi Metode Pembelajaran Index Card Match Pada Materi Sejarah Kebudayaan Islam di MDTA AL Hidayah - Aditiya Jaya Permana; Kiran Saputra Koeswito; Torik Miftah Fadil; Muhamad Hasan Al Wustha; Muhamaf Fadlil; Lesi Oktiwanti (Rengganis Jurnal Pengabdian Masyarakat, 2026)
The teacher centered approach in learning Islamic Cultural History often leads to low student participation and understanding. This community service activity aims to implement a participatory learning model using the Index Card Match technique combined with storytelling for 6th-grade students at MDTA Al-Hidayah. The method followed a structured process: opening, core activities (storytelling and card matching), closing, and evaluation. Data were collected through pre-tests, post-tests, and observation sheets. Results showed a significant increase in students' cognitive scores, from an average of 59 to 89.5, with a Wilcoxon test significance of 0.000. Furthermore, 18 out of 19 students showed improved learning outcomes. The evaluation instrument also met high validity standards with an index of 0.891. In conclusion, the combination of Index Card Match and storytelling effectively enhances student engagement and understanding of Islamic history, proving that active learning models are highly applicable in religious education contexts.